Artistic presentation of seizure semiology—A remarkable painting Künstlerische Darstellung von Anfallssemiologie – ein besonderes Gemälde - Schiele, Martina; Kasper, Burkhard S. (Clinical Epileptology, 2025)
A painting is shown that depicts the seizure semiology of a patient, i.e., Martina Schiele the painter and co-author of this article. It is illustrated that the artistic act helped to express and better understand her symptoms, which were hardly describable in words. A contextualisation and perspective on epilepsy and art is given.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Art; Aura; Epilepsy; Neurology; Neuroscience